Effect of Zinc on Growth, Plant Yield, NPK Uptake and Economics - Palai, Jnana Bharati; Sarkar, N. C.; Jena, Jagadish (International Journal of Bio-resource and Stress Management, 2017)
The experiment was conducted at agricultural farm of Palli Siksha Bhavana, Visva-Bharati at Sriniketan of Birbhum district, West Bengal during pre-rabi season of 2015 to study the effect of zinc on growth and productivity of baby corn. The soil at experimental site was analysed sandy loam in texture with low in available N, medium in available P2O5 and K2O and slightly acidic (pH: 4.78) in nature. The experiment was carried out in RBD with 8 treatments. Each treatment was replicated thrice and the different treatments viz. absolute control, soil application of Zn @ 6 kg ha-1, soil application of Zn @ 10 kg ha-1, seed treatment @ 0.6% Zn, seed treatment @ 1.2% Zn, one foliar spray @ 0.05% Zn at 25 DAS, soil application of Zn @ 6 kg ha-1+one foliar spray @ 0.05% Zn, seed treatment @ 0.6% Zn+one foliar spray of 0.05% Zn at 25 DAS. At tasseling stage, growth attributes like highest number (9.3) of leaves, maximum (3220 cm2, 4.0) leaf area and LAI, respectively, highest (26.4 g m-2 day-1) CGR and maximum (47.2 days) LAD were resulted with soil application of Zn @ 6 kg ha-1+one foliar spray @ 0.05% Zn at 25 DAS. On the other hand, at tasseling stage, highest (11.3 g m-2 day-1) NAR were produced by seed treatment @ 0.6% Zn+one foliar spray @ 0.05% Zn at 25 DAS. However, soil application of Zn @ 6 kg ha-1+one foliar spray @ 0.05% Zn at 25 DAS (T7) recorded highest (59.06 kg ha-1) N uptake, maximum (11.8 kg ha-1) P uptake and highest (32.51 kg ha-1) K uptake which was significantly higher than all other treatments.Moreover highest net return (Rs. 165442 ha-1) as well as B:Cratio were found with the soil application of Zn @ 6 kg ha-1+one foliar spray @ 0.05% Zn at 25 DAS.